The Effect Of Financial Literacy On Household Interest In Utilizing Insurance Financial Products - Kadek Ayu Santhi Novitasari; Ni Putu Wiwin Setyari (Universitas Udayana, 2025)
Insurance is needed to provide financial protection. However, Household trust in insurancefinancial products and services is lower than in banking, especially in Bali Province. Financialliteracy is needed to increase trust in insurance financial services. This research aims to examinethe condition of financial literacy at the household level in Bali Province and analyze the influenceof financial literacy on household interest in utilizing insurance financial service products in BaliProvince. This research used a quantitative associative approach with survey data collectiontechniques using questionnaires. The data analysis technique for this research uses the formationof index numbers to measure the financial literacy index at the household level in Bali Provinceand Binary Logistic Regression to determine the influence of the independent and dependentvariables. The analysis results show that the financial literacy index in Bali province is in the highcategory, and financial literacy has a significant relationship with household interest in utilizinginsurance financial services.